The Influence of Financial Literacy and Innovation on The Use of BSI Digital Services in Parepare, Indonesia - Anugrah, Mahamad Azhar; Musmulyadi, M.; Nurfadhilah, N.; Trian Fisman Adisaputra (Manunggal Halim Jaya, 2025)
This study aims to analyze financial literacy and innovation's influence on the decision to use Bank Syariah Indonesia (BSI) digital services in Parepare City. The research method uses a quantitative approach with multiple regression analysis. Data was obtained through research instruments tested for validity and reliability. The results showed that financial literacy had a positive and significant effect with a regression coefficient of 0.350 (p < 0.05), and financial innovation also had a positive and significant effect with a regression coefficient of 0.355 (p < 0.05) on the decision to use BSI digital services. Simultaneously, these two variables had a significant influence with an F-count value of 50.794 (p < 0.05) and could explain 51.2% of the variation in the decision to use BSI services. This study concludes that increasing financial literacy and developing banking service innovations are important in encouraging BSI digital services in Parepare City.